Discovery of N2-(4-Amino-cyclohexyl)-9-cyclopentyl- N6-(4-morpholin-4-ylmethyl-phenyl)- 9H-purine-2,6-diamine as a Potent FLT3 Kinase Inhibitor for Acute Myeloid Leukemia with FLT3 Mutations - Gucký, Tomáš; Řezníčková, Eva; Radošová Muchová, Tereza; Jorda, Radek; Klejová, Zuzana; Malínková, Veronika; Berka, Karel; Bazgier, Václav; Ajani, Haresh; Lepšík, Martin; Divoký, Vladimír; Kryštof, Vladimír (Journal of medicinal chemistry, 2018)
FLT3 tyrosine kinase is a potential drug target in acute myeloid leukemia (AML) because patients with FLT3-ITD mutations respond poorly to standard cytotoxic agents and there is a clear link between the disease and the oncogenic properties of FLT3. We present novel 2,6,9-trisubstituted purine derivatives with potent FLT3 inhibitory activity. The lead compound 7d displays nanomolar activity in biochemical assays and selectively blocks proliferation of AML cell lines harboring FLT3-ITD mutations, whereas other transformed and normal human cells are several orders of magnitude less sensitive. The MV4-11 cells treated with 7d suppressed the phosphorylation of FLT3 and its downstream signaling pathways, with subsequent G1 cell cycle arrest and apoptosis. Additionally, a single dose of 7d in mice with subcutaneous MV4-11 xenografts caused sustained inhibition of FLT3 and STAT5 phosphorylation over 48 h, in contrast to the shorter effect observed after administration of the reference FLT3 inhibitor quizartinib.
Keywords: Leukemia, Myeloid, Acute; tyrosinkinasa 3 podobná fms; inhibitory proteinkinas; simulace molekulového dockingu; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; Diamines; Protein Conformation; Molecular Docking Simulation; Antineoplastic Agents; zvířata; myši; Mice; xenogenní modely - testy protinádorové aktivity; Protein Kinase Inhibitors; objevování léků; nádorové buněčné linie; protinádorové látky; fms-Like Tyrosine Kinase 3; diaminy; Xenograft Model Antitumor Assays; Animals; Cell Line, Tumor; Drug Discovery; akutní myeloidní leukemie; konformace proteinů